Teacher’s awareness of the integrated environmental education curriculum in South Africa - Damoah, Benjamin; Adu, Emmanuel Olusola (Penerbit Universiti Kebangsaan Malaysia, 2020)
The study focuses on teacher’s awareness of the integrated environmental education curriculum as prescribed in the current curriculum and assessment policy statement (CAPS) document in South Africa. The study examines challenges confronting teachers in the process of integrating environmental education into their respective subject areas of speciality. The role of teachers in the implementation of environmental education in developing an environmentally literate citizenry is of great significance. It was recommended among others that; the government should develop curriculum with clear goals and content with specific guideline which shall develop teachers’ capacity in the teaching of environmental education. Successful implementation of any educational policy, largely depends on teacher’s competencies. The findings suggest that, department of basic education should appoint subject advisors to equip and resource teachers in order to implement EE integration successfully. The study further concluded that, the policy has failed to spell out a clear direction on how teachers should integrate EE into their subjects. EE integration is doable theoretically but practically, it has failed to achieve the anticipated results due to the numerous problems confronting its implementation in the classroom.